2011
DOI: 10.1007/s12253-011-9413-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of the Angiogenetic Network of VEGF, HIF1α, VEGFR-2 and Endothelial Nitric Oxide Synthase (eNOS) in Human Breast Cancer

Abstract: In breast cancer cases, the major molecules regulating NO and VEGF production can be co-expressed in the individual carcinomas implying a possibility for the relevant pathways to be active; however appropriate functional experiments remain to be conducted to prove such a hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
2
8
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first survival study investigating the potential prognostic value of VEGFR‐2. In accordance with previous IHC reports in human breast cancer, we did not find any significant relationship between VEGF or VEGFR‐2 expressions and tumour size, lymph node status or patient overall and DFS . Similarly, Millanta et al also reported that VEGF does not influence the survival time of female dogs with MMTs .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first survival study investigating the potential prognostic value of VEGFR‐2. In accordance with previous IHC reports in human breast cancer, we did not find any significant relationship between VEGF or VEGFR‐2 expressions and tumour size, lymph node status or patient overall and DFS . Similarly, Millanta et al also reported that VEGF does not influence the survival time of female dogs with MMTs .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, VEGFR‐2 was expressed in the endothelial cells of the intra‐tumoural vasculature and the mammary cancer epithelial cells, while VEGF was mainly detected in the neoplastic cells. As previously described in human and canine mammary tumours, VEGF expression was significantly associated with the presence of VEGFR‐2 in cancer cells, supporting the existence of an autocrine VEGF/VEGFR2 loop . In women breast cancer, it has been postulated that this loop integrates signalling pathways for cancer cell proliferation and resistance to apoptosis .…”
Section: Discussionsupporting
confidence: 67%
“…Positive staining (3+) for Her-2 corresponded to strong staining in >30% of tumor cells, whereas weak to moderate staining in >10% cells was scored as equivocal (2+), and no staining or faint incomplete staining was scored as negative (−) or faint (1+)20. For VEGF staining, intensity of cytoplasmic immunostaining was scored from 0 to 3+ (no staining to strong staining, respectively)21. Vimentin, AACT, desmin, S-100, CK, EMA, CD68 or CD163 staining was considered positive if cell staining was either in the cytoplasm, membrane, or nucleus.…”
Section: Methodsmentioning
confidence: 99%
“…AKT1-knockout mice showed impaired vascular maturation with decreased expression of TSP-1 and TSP-2, while reexpression of TSP-1 and TSP-2 in mice transplanted with wild-type bone marrow is associated with the angiogenesis [39]. The endothelial NOS (eNOS) is critical for VEGF-triggered postnatal angiogenesis [40, 41]. Several protein kinases, such as Akt, AMP-activated protein kinase (AMPK), and protein kinase A (PKA), are known to activate eNOS [42].…”
Section: Downstream Molecules Mediated By Pi3k/akt/pten In Regulatmentioning
confidence: 99%